Crucial Factors That Influence Early Marriage Among Teenagers in Kebungson Village, Gresik District - Cahyono, Muhammad Kharis (GoAcademica Research & Publishing, 2025)
Adolescence is a transition period from childhood to early adulthood. So, in the development phase, adolescents will experience changes. Because this transition period can cause individuals to face many problems. These problems arise because individuals are in the process of searching for their identity. Psychological and psychological changes can influence changes in attitudes that will be displayed by individuals. Things that are often faced by adolescents are conflicts with social roles or what are usually called wrong associations in their surroundings. Early marriage which is a phenomenon now is basically a cycle of recurring phenomena and does not only occur in rural areas which are influenced by minimal awareness, although it also often occurs in urban areas which are indirectly influenced by their own lifestyle. Early marriage occurs because of the changing era that is more advanced and the increasing development of digital from year to year which results in the mindset of each individual, especially adolescents, no longer considering marriage to be something sacred and worthy of respect and carried out properly and correctly according to the government and beliefs that are believed. This study uses qualitative research techniques. This study used 2 research subjects with different backgrounds in terms of making decisions to have early marriage.